Financial Management: Some Important Generalizations - Karl Kepner; Allen Wysocki (EDIS, 2002)
This is EDIS document FE 343, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2002. The objectives of this article on financial management are twofold: (1) to provide an overview of the importance of professional financial management to a business firm’s operations and (2) to discuss nine financial management viewpoints that tend to restrict the financial performance of business organizations.